Clinical and radiological efficacy of a new conservative treatment for fibrocystic disease - R. M. Shabaev; I. V. Kolyadina; D. A. Blagovestnov; P. M. Starokon (Опухоли женской репродуктивной системы, 2024)
Background. Long-lasting dyshormonal breast diseases in women represent a risk factor for breast cancer, especially in patients with atypia. Clinical manifestations of fibrocystic breast disease (FBD) and mastopathy, including high-intensity pain cause psychoemotional discomfort and reduce the quality of life of women. The search for effective management strategies for mastopathy with an antiproliferative effect is highly relevant.Aim. To assess clinical and radiological efficacy of a new conservative treatment for FBD, “Evening primrose oil” administered orally for 6 months in women with symptomatic FBD.Materials and methods. This randomized, blind, placebo-controlled trial included 144 patients with clinical FBD manifestations (pain and tension in the breast). Patients were randomly assigned to one of the two treatment groups. Women in group I received “Evening primrose oil”, whereas women in group II received placebo (ascorbic acid) for 6 months. We measured the dynamics of radiological findings (at mammography and ultrasound examination) in the breast before and after treatment, as well as pain intensity using the visual-analog scale.Results. Patients in group I with all types of FBD (diffuse mastopathy, nodular, and mixed forms) demonstrated positive dynamics and BI-RADS category downgrading within 6 months. In the placebo group, the examination after 6 months demonstrated no significant changes in the breast and no BI-RADS category downgrading among women with diffuse mastopathy. Some patients with nodular and mixed FBD receiving placebo had negative dynamics after 6 months (as demonstrated by mammography and ultrasound examination; BI-RADS category upgraded from II to III, p<0.01). Patients receiving “Evening primrose oil” also showed positive dynamics in their clinical manifestations, including decreased breast pain (from 7.8 to 1.8 on the visual analog scale). By contrast, patients receiving placebo had no changes in their breast pain intensity after 6 months (from 7.3 to 7.1 on the visual analog scale), which resulted in poorer psychoemotional state in 55.6 % of women.Conclusion. Our new treatment strategy for FBD patients with clinical and radiological manifestations in the breast demonstrated high efficiency and can be implemented into routine clinical practice.